Clones promissores de seringueira para a região do Vale do Ribeira, São Paulo - GONÇALVES, PAULO DE SOUZA; SAES, LUIZ ALBERTO; Furtado, Edson Luiz [UNESP]; SAMBUGARO, ROSANA; SAKAI, MAURO (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2000)
Este trabalho objetivou apresentar resultados da primeira seleção de clones de seringueira (Hevea brasiliensis (Willd. ex Adr. de Juss.) Muell.Arg.) da série IAC 300, e amazônicos das séries IAN e Fx, em experimento de pequena escala, visando produção, crescimento e resistência ao mal-das-folhas. A produção e o vigor de 20 clones foram avaliados por dois e nove anos, respectivamente, em PariqüeraAçú, no Vale do Ribeira, SP. Os clones IAC 301, IAC 304, IAC 306 e IAC 319 produziram satisfatoriamente nos dois primeiros anos de sangria. Os clones amazônicos IAN 6323, Fx 3864 e IAN 2903, com produções de 1.078 kg, 945 kg e 900 kg/ha/ano, respectivamente, foram superiores à testemunha IAN 873 (878 kg/ha/ano). Os clones selecionados apresentaram crescimento vigoroso, com extremos de perímetro do caule, na abertura do painel, de 37,40 cm (IAN 4493) a 53,75 cm (IAN 6323), e percentual de plantas aptas à sangria de 7,0% (IAN 4493) a 100% (IAN 6323 e IAC 302), exceto os clones Fx 3899 e IAN 3044. O IAC 315, com 7,37 mm, mostrou maior espessura de casca virgem que o IAN 873 (6,44 mm). Os clones IAC 320, IAC 306 e IAC 315 foram os mais resistentes ao Microcyclus ulei.

The objective of this paper was to show first selection results of IAC 300 and Amazonian IAN and Fx series of rubber tree (Hevea brasiliensis (Willd. ex Adr. de Juss) Muell.Arg.) clones in small scale trial evaluation, for yield, growth and SALB performance. Yield and vigour of 20 clones were assessed for two and nine years, respectively, in Vale do Ribeira, SP, Brazil. In the IAC 300 serie, four clones (IAC 301, IAC 304, IAC 306 and IAC 319) were classified as satisfactory in yielding. The Amazonian clones IAN 6323, Fx 3864 and IAN 2903 produced 1,078 kg, 945 kg and 900 kg/ha/year, respectively, higher than the control IAN 873 (878 kg/ha/year). All selected clones had vigorous growing, with the girth at opening (cm) ranging from 37.40 (IAN 4493) to 53.75 (IAN 6323) and tappability ranging from 7.0% (IAN 4493) to 100% (IAC 6323 and IAC 302), except for Fx 3899 and IAN 3044. The IAC 315, with 7.37 mm, had bigger thickness virgin bark than IAN 873 (6.44 mm). Concerned to SALB performance, clones IAC 306, IAC 315, IAC 320 were the best in resistance.
Promising hevea clones for Ribeira River Valley Region, São Paulo State, Brazil
Keywords: Hevea brasiliensis; crescimento; rendimento; sangria; resistência a pragas; Hevea brasiliensis; growth; yields; tapping; pest resistance